Danger of Slippery Slopes in Nudge Research - Siipi, Helena (Springer Science and Business Media LLC, 2026)
Nudges are a way to steer people's behavior through changes in how choices are presented. Nudge research has been incorporated into public policy in many countries, and nudge research, thus, has the potential to directly influence societies and individuals. As a result, research ethics for nudge research is needed to ensure that nudges developed are not instances of unethical manipulation of people. In this paper, I argue that two types of slippery slopes from ethically fine nudges to ethically problematic ones can take place in nudge research. The conceptual slippery slope follows from (1) the broad way of defining nudges, (2) the multitude of different ways of understanding manipulation of people, (3) many manipulation definitions implying that some nudges are manipulative, and (4) some forms of manipulation of people being prima facie wrong. The empirical slippery slope rests, first, on the possibility of small steps from ethically acceptable to wrong nudges, and second, on the cognitive limits typical to human beings (including nudge researchers). Both slippery slope arguments imply the need to of nudge researchers to create so-called firebreaks. The firebreaks can take the form of ethical justifications. To avoid slippery slopes, certain types of arguments should be excluded from these justifications.